2015
DOI: 10.3138/jcfs.46.2.265
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Maternal Parenting Style and High School Achievement and Self–Esteem in China, Turkey and U.S.A.

Abstract: This cross-cultural study investigated country differences in the relationship between maternal parenting styles and two important developmental outcomes of students – high school achievement and self-esteem. 634 undergraduates resident in three countries (China 207, Turkey 196, USA 231) where socio-cultural orientation and previous research suggest that normative family relationships would be different, were selected. We predicted that in the three countries, different maternal parenting styles would be preva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0
6

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 53 publications
2
11
0
6
Order By: Relevance
“…Interestingly, the behavioral control style of parenting influenced positively indirectly through the maternal help decoding and reading comprehension skills in the LM group. The result confirms earlier research that demonstrated the positive relations of relative warm and authoritative parenting with moderate control, which also offers a positive outcome in school achievement (Steinberg et al 1989;Cox and Paley 2003;Landry et al 2006;Fletcher et al 2008;Newman et al 2015). The parenting style of LM mothers can be explained in terms of warm mother-daughter relationships and mothers' trust in their children's abilities (see Sikiö, Holopainen, Siekkinen, Silinskas, Lerkkanen and Nurmi 2016), which strengthen intrinsic motivation.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Interestingly, the behavioral control style of parenting influenced positively indirectly through the maternal help decoding and reading comprehension skills in the LM group. The result confirms earlier research that demonstrated the positive relations of relative warm and authoritative parenting with moderate control, which also offers a positive outcome in school achievement (Steinberg et al 1989;Cox and Paley 2003;Landry et al 2006;Fletcher et al 2008;Newman et al 2015). The parenting style of LM mothers can be explained in terms of warm mother-daughter relationships and mothers' trust in their children's abilities (see Sikiö, Holopainen, Siekkinen, Silinskas, Lerkkanen and Nurmi 2016), which strengthen intrinsic motivation.…”
Section: Discussionsupporting
confidence: 87%
“…Moreover, only mothers reported their parenting styles and levels of help with homework. Research demonstrates that mothers and fathers have different roles in parenting and that these roles vary by country (Newman et al 2015). This aspect would have been interesting to study alongside the impact of fathers' parental involvement, but their response rate was too low.…”
Section: Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the contemporary setting, filial piety and parental authority in China has potentially undergone significant change, not unlike its economy and social structure. Although Chinese parents are often depicted as being authoritarian, such parenting styles do not always yield the results desired by the parents (Newman et al., ). While better performance in school has been linked to authoritarian parenting (e.g., Wang, Pomerantz, and Chen, ), Chinese children's self‐esteem has been shown to be deleteriously impacted by authoritarian parenting (e.g., Shek, ).…”
Section: Filial Piety and Parental Authoritymentioning
confidence: 99%
“…Highly educated parents more involved in scientific activities such as seminars, workshops of child development. Newman et al showed that parents' education level correlated with adolescent's self-esteem, [30] the higher the parent's education level, the higher the adolescent self-esteem which associated with parental assistance [30]. High education level makes parents able to receive more information about appropriate childcare [29].…”
Section: Discussionmentioning
confidence: 99%